Hey, pancakes! - Weston, Tamson; Gammell, Stephen (San Diego : Harcourt, 2005)
The day gets off to a rough start, but soon the smell of pancakes fills the air and a family gathers for a breakfast feast.
G1
Keywords: Pancakes, waffles, etc. -- Fiction; Breakfasts -- Fiction; Family life -- Fiction; Stories in rhyme; Humorous stories